Numerical research on the turbulent drag reduction mechanism of a transverse groove structure on an airfoil blade. Issue 1 (1st January 2019) - Wu, Zhengren; Li, Shuguang; Liu, Mei; Wang, Songling; Yang, Hongyue; Liang, Xiujun
Abstract : The optimization of the airfoil has a significant impact on the reduction of energy consumption for a rotary machine. In this paper, ANSYS Fluent is used to study the influence of different groove structure sizes on the turbulence drag of NACA0012 airfoil blades, and the drag reduction mechanism is analyzed. The results show that the groove structure can significantly reduce the drag during the working speed of the fan. The optimal groove size is s = 0.1 mm and the drag is reduced by 9.65%. The secondary vortices reduce the normal velocity gradient at the top of the groove structure, resulting in a reduction in viscous drag. However, as the groove size increases, the drag reduction effect decreases, and even the drag increases. The overall shear stress of the airfoil surface with the transverse groove structure is smaller than the original airfoil, and the velocity gradient of the airfoil surface is reduced. The two sides work together to reduce the turbulence drag of the airfoil. Besides, the spacing between the grooves increases the shear stress in some areas, but reduces the mutual interference of the vortices, so there is an optimum value for the groove spacing.